2017
DOI: 10.1186/s12912-017-0268-5
|View full text |Cite
|
Sign up to set email alerts
|

Communication skills intervention: promoting effective communication between nurses and mechanically ventilated patients

Abstract: BackgroundPatients in the Intensive Care Unit (ICU) often experience communication difficulties - usually associated with mechanical ventilation - resulting in psychological problems such as anxiety, fear, and depression. Good communication between nurses and patients is critical for success from personalised nursing care of each patient. The purpose of this study is to describe nurses’ experience of a communication skills training intervention.MethodsA convenience sample of twenty intensive care nurses partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 19 publications
0
32
0
10
Order By: Relevance
“…Therefore, it is important for nurses to consider these factors when communicating with patients in order to identify their communication needs and manage accordingly (Daly 2017). Furthermore, Dithole et al (2017) and Norouzinia et al (2016) In this case model, the nurse acknowledged she was privileged to be a guest in Audrey's home, so she tailored her strategy to gain Audrey's perspective. The nurse's aim was to get Audrey involved in her care decision-making since Audrey knows herself better.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important for nurses to consider these factors when communicating with patients in order to identify their communication needs and manage accordingly (Daly 2017). Furthermore, Dithole et al (2017) and Norouzinia et al (2016) In this case model, the nurse acknowledged she was privileged to be a guest in Audrey's home, so she tailored her strategy to gain Audrey's perspective. The nurse's aim was to get Audrey involved in her care decision-making since Audrey knows herself better.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the training of professionals took place through direct conversations within the ICU through printed summaries of the usability of the devices left for the patient and through seminars organized by the head of the service. Dithole et al (2016Dithole et al ( , 2017 pointed out the importance of studies and training in resource management, and other strategies that can be adopted together with the coordination of the sector, such as specialized training actions and allocation of more resources. Also, the study by Happ et al (2011) reported that, without training in AEC techniques, nurses who work in intensive care do not have the set of skills in strategies necessary to favor the communication of their patients most severely affected by communication restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Los pacientes en la UCI por su gravedad vital y patología a menudo experimentan dificultades de comunicación, éstas generalmente asociadas a la ventilación mecánica y la presencia del tubo endotraqueal incapacitándolo para hablar, ( 16) siendo éste una gran limitante al momento de comunicarse lo que provoca problemas psicológicos como ansiedad, miedo y depresión. (10) En cuanto a la percepción de los pacientes, refieren sentirse impotentes y frustrados al no poder usar su voz, muchos mencionan haber intentado gritar para llamar al profesional de enfermería, aun sabiendo que no podían, provocando sentimientos de frustración. La incapacidad para hablar se experimentó como "no poder hacer nada", como si la ausencia de voz bloqueara las demás acciones humanas de comunicación.…”
Section: Percepción Del Paciente Sobre La Comunicación Enfermero-pacienteunclassified